Seasonal damage caused by herbivorous insects on Caryocar brasiliense (Caryocaraceae) trees in the Brazilian savanna - DEMOLIN-LEITE, GERMANO LEÃO; DOS SANTOS VELOSO, RONNIE VON; COLA-ZANUNCIO, JOSÉ; MAIA-ALMEIDA, CHRYSTIAN IEZID; FIÚZA-FERREIRA, PAULO SÉRGIO; SERRÃO, JOSÉ EDUARDO; RAMALHO, FRANCISCO DE SOUZA (Revista Colombiana de Entomología, 2012)
Caryocar brasiliense (Caryocaraceae) trees have a wide distribution in the Brazilian savanna. This plant is protected by federal laws and is untouched in deforested areas of the Brazilian savanna. This situation increases the damage to leaves, flowers, and fruits from chewing insects. We studied populations of herbivorous Lepidoptera, Coleoptera, and Hymenoptera and their natural enemies on C. brasiliense trees for three successive years during each season in the Brazilian savanna. Phytophagous insects were most abundant at the beginning of winter and with more species and diversity in the summer. Natural enemies were most abundant in the spring and in the winter and with highest species and diversity at end of the winter. Fruits bored by Carmenta sp. (Lepidoptera: Sesiidae) and Naupactus sp.3 (Coleoptera: Curculionidae) on the leaves were highest in the summer. Fruits scraped by Naupactus sp.1 and sp.2 were more numerous in the spring and summer, percentage of defoliation in the autumn. Apoptus sp. (Coleoptera: Elateridae) on the leaves in the spring, and leaf miners (Lepidoptera) in the winter. In the case of natural enemies, Crematogaster sp. (Hymenoptera: Formicidae) were most abundant on the leaves and in the flowers in the winter and spring, and on the fruits in the spring when new leaves and flowers are formed. The number of Zelus armillatus (Hemiptera: Reduviidae), Holopothrips sp. (Thysanoptera: Phlaeothripidae), and the complex of spiders were greater on the leaves in the winter; and Trybonia sp. (Thysanoptera: Phlaeothripidae) was most abundant on the leaves in the autumn.